Pyro Corporation : sound fire extinguisher / Mohammad Farhan Kamal Ariffin ...[et al.] - Kamal Ariffin, Mohammad Farhan; Abd Aziz, Mohd Safwan; Abdul Latif, Amir Lutfi; Baharuddin, Muhamad Adib Azizi; Zulkarnain, Ashraf (2016)
As for the business, we are providing a special and innovation fire extinguisher for Malaysian. As we go thru with the changes of environment, people nowadays more concern about environment and want to friendly user. So, our surveying we conclude that we are going to provide the Malaysia with the simple and special fire extinguisher that are well in high product's quality and high efficiency product.